2021
DOI: 10.3390/jpm11070681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytokines as Robust Diagnostic Biomarkers for COVID-19 Detection

Abstract: Antigen tests or polymerase chain reaction (PCR) amplification are currently COVID-19 diagnostic tools. However, developing complementary diagnosis tools is mandatory. Thus, we performed a plasma cytokine array in COVID-19 patients to identify novel diagnostic biomarkers. A discovery–validation study in two independent prospective cohorts was performed. The discovery cohort included 136 COVID-19 and non-COVID-19 patients recruited consecutively from 24 March to 11 April 2020. Forty-five cytokines’ quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…A total of 136 patients were registered in the study. Clinical characteristics of patients are shown in Discovery cohort panel of Table 1 in Tamayo-Velasco et al [ 21 ]. In terms of age, there were no differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 136 patients were registered in the study. Clinical characteristics of patients are shown in Discovery cohort panel of Table 1 in Tamayo-Velasco et al [ 21 ]. In terms of age, there were no differences.…”
Section: Resultsmentioning
confidence: 99%
“…Differences between groups were assessed as described in Tamayo-Velasco A et al [ 21 ]. Differences in oxidative stress molecules' levels between groups were assessed using the Mann Whitney U test.…”
Section: Methodsmentioning
confidence: 99%
“…Other critical hub-high traffic genes in the blue module included EP300 ( 146 , 147 ), CDK1 ( 4 , 148 ), VEGFA ( 149 151 ), CTNNB1 ( 151 , 152 ), IL10 ( 9 , 153 155 ), SOCS1 , SOCS3 ( 156 ), SIRT1 ( 157 , 158 ), TFRC ( 159 161 ), HSP90AB1 ( 162 ), CYCS ( 163 ), EZR ( 164 ), TNFAIP3 , ICAM1 ( 10 ), and PIK3R1 ( 139 ) as well as TFs such as ATF4 ( 165 ), ATF3 ( 166 , 167 ), and BCL6 ( 152 ) which have important roles in pathogenesis of SARS-CoV-2, and some of which are potential therapeutic targets. For instance, SOCS1 / 3 antagonists may be prophylactic or therapeutic against the COVID-19 pandemic ( 156 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar macrophage activation and neutrophil recruitment are first key events of innate immune activation in response to SARS-CoV-2 and the presence of alveolar damage-associated molecular patterns. A very recent study identified IP-10 (CXCL10) as key predictive cytokine for disease progression to severe courses of illness [45] with LRT involvement. Of note, IP-10 is a chemokine for recruitment of macrophages in response to viral invasion and tissue damage, but also acts as regulator of cell growth and proliferation [46].…”
Section: Discussionmentioning
confidence: 99%